Isolation and Identification of Indonesian Lactobacillus reuteri strain from Saliva of Young Adults - Armelia Sari Widyarman; Stella Pranoto; Citra Fragrantia Theodorea; Endang Winiati Bachtiar; Boy Muchlis Bachtiar (Faculty of Dentistry, Universitas Trisakti, 2018)
Background: Biofilms are involved in a wide variety of microbial infections, including dental caries and periodontitis. The use of probiotics has been a promising prevention and treatment modality with which to combat biofilm-related diseases in the oral cavity. The probiotic Lactobacillus reuteri has been proven to reduce gingivitis and plaque index inside the oral cavity. These bacteria can be found in the digestive system and also in the human oral cavity. Objective: The aim of this study was to identify L. reuteri in the saliva of Indonesian young adults. Methods: Forty saliva samples were collected from 18–24 year-old Indonesian subjects. DNA extraction was performed, and then, the identification of L. reuteri was accomplished using PCR. Six subjects showed positive results. The positive samples were cultured in Rogosa Agar for 24 hours at 37°C anaerobically. Several single colonies were further cultured separately in broth medium before DNA extraction and PCR identification were performed. The four thickest bands were selected for DNA sequencing. Results: An analysis performed using BLAST showed that two of the L. reuteri strains obtained from the Indonesian saliva isolates had 96% (isolate 3.11) and 95% (isolate 5.14) values. This confirmed the presence of new strains based on average nucleotide identity (ANI). The isolate strains of 3.11 and 5.14 have been registered at DDBJ/EMBL/GenBank under the accession number LC382415 and LC382416, respectively. Conclusion: L. reuteri novel strain can be isolated from the saliva of Indonesian young adults. Further studies involving biochemical tests and phenotypic analysis are needed to better understand these new L. reuteri strains.